The simple measurement of residue curves and the associated VLE data for ternary liquid mixtures - Chronis, Theodoros (My University, 1996)
An apparatus to measure residue curves and the associated VLE data was designed. The apparatus was required to measure this data quickly, easily, cheaply and reasonably accurately. The Acetone, Benzene and Chloroform and the Acetone, Methanol and Benzene ternary liquid systems were measured to test the accuracy of the apparatus. In both cases, the results obtained correlated reasonably well with those predicted by theory using published data. [Abbreviated Abstract. Open document to view full version]
A dissertation submitted to the Faculty of Engineering, University of the Witwatersrand, Johannesburq, in fulfilment of the requirements for the degree of Master of Science in Engineering. Johannesburg, 1996.
Keywords: Vapor-liquid equilibrium